Nitrergic signaling via interstitial cells of Cajal and smooth muscle cells influences circular smooth muscle contractility in murine colon. Issue 6 (29th January 2018) - Beck, K.; Friebe, A.; Voussen, B.
Abstract: Background: Regulation of gastrointestinal motility involves excitatory and inhibitory neurotransmission. Nitric oxide (NO), the major inhibitory neurotransmitter, acts via its receptor NO‐sensitive guanylyl cyclase (NO‐GC). In the GI tract, NO‐GC is expressed in several cell types such as smooth muscle cells (SMC) and interstitial cells of Cajal (ICC). Using cell‐specific knockout mice, we have previously shown that NO‐GC modulates spontaneous contractions in colonic longitudinal smooth muscle. However, its detailed role in the colonic circular smooth muscle is still unclear. Methods: Myography was performed to evaluate spontaneous contractions in rings of proximal colon (2.5 mm) from global (GCKO) and cell‐specific knockout mice for NO‐GC. Immunohistochemistry and in situ hybridization were used to specify NO‐GC expression. Key results: Colonic circular smooth muscle showed three different contraction patterns: high‐frequency ripples, slow phasic contractions, and large contractions. Ripples formed independently of NO‐GC. Slow phasic contractions occurred intermittently in WT, SMC‐GCKO, and ICC‐GCKO tissue, whereas they were more prominent and prolonged in GCKO and SMC/ICC‐GCKO tissue. Tetrodotoxin and the NO‐GC inhibitor ODQ transformed slow phasic contractions of WT and single cell‐specific knockout into GCKO‐like contractions. ODQ increased the frequency of large contractions in WT and ICC‐GCKO colon but not in GCKO, SMC‐GCKO, and SMC/ICC‐GCKO preparations. Tetrodotoxin and hexamethonium abolished large contractions. Conclusions and Inferences: We conclude that short rings of murine colon can be effectively used to record spontaneous contractions. Although NO‐GC in SMC determines smooth muscle tone, concerted action of NO‐GC in both SMC and ICC modulates slow phasic contractions and large contractions. Abstract : Murine colonic circular smooth muscle showed three different contraction patterns: high frequency ripples, slow phasic contractions and large contractions. Ripples formed independently of NO/cGMP signaling whereas NO‐sensitive guanylyl cyclase in smooth muscle cells and interstitial cells of Cajal modulated slow phasic contractions and large contractions. We conclude that short rings of murine colon can be effectively used to investigate nitrergic effects on spontaneous contractions.